KAJIAN CEMARAN MIKROBIOLOGIS CILOK DAN SAUS KACANG DI KOTA SURAKARTA - Eko Yuliastuti; Nanik Suhartatik; Akhmad Mustofa; Desy Lustiyani; Nanda Pratiwi (AGROINTEK, 2021)
Cilok was a traditional food originating from Bandung and comes from the abbreviation of "Aci dicolok". As the name implies, a snack made from tapioca flour mixed with condiment and sometime using meat or fish fillet. It was tasty and chewy. Cilok has quietly different from meatball because meatball using wheat flour. Cilok usually consumed using a sauce made from crushed peanuts, sugars, salt, mixed with chili sauce, tomato sauce, or soy sauce which can be modified as you want. Recently, cilok sales in the city of Surakarta have become increasingly popular. In almost every corner we can find cilok sellers. This study aims to determine the level of microbiological contamination found in cilok and peanut sauce in Surakarta. The research method used was simple random sampling method from 5 districts in Surakarta. The number of contaminants was calculated by the direct plate count method. The tests performed were to determine the total plate count (ALT), total Staphylococci, total Salmonella shigella, and total coliforms of the cilok and also for the sauce. As for the cilok sample, the average log value of ALT was 6.57 - 7.97 log CFU / g, total Staphylococci 4.57 - 4.96 log CFU / g, Salmonella shigella was 0.53 - 1.23 log CFU / g, and total coliforms 1.00 - 2.26 log CFU / g. Peanut sauce sample, the average log value of ALT was 7.40 - 8.18 log CFU / g, total staphylococci 5.84 - 6.68 log CFU / g, total Salmonella shigella was 2.24 - 3.23 log CFU / g, and Escherichia coli 2.35 - 5.79 log CFU / g. From the test results of the peanut sauce and peanut sauce samples, it can be concluded that the peanut sauce and peanut sauce sold in Surakarta are still not suitable for consumption.